Layered Oxide, Graphite and Silicon-Graphite Electrodes for Lithium-Ion Cells: Effect of Electrolyte Composition and Cycling Windows. Issue 1 (14th October 2016) - Klett, Matilda; Gilbert, James A.; Pupek, Krzysztof Z.; Trask, Stephen E.; Abraham, Daniel P.
Abstract : The electrochemical performance of cells with a Li1.03 (Ni0.5 Co0.2 Mn0.3 )0.97 O2 (NCM523) positive electrode and a blended silicon-graphite (Si-Gr) negative electrode are investigated using various electrolyte compositions and voltage cycling windows. Voltage profiles of the blended Si-Gr electrode show a superposition of graphite potential plateaus on a sloped Si profile with a large potential hysteresis. The effect of this hysteresis is seen in the cell impedance versus voltage data, which are distinctly different for the charge and discharge cycles. We confirm that the addition of compounds, such as vinylene carbonate (VC) and fluoroethylene carbonate (FEC) to the baseline 1.2 M LiPF6 in ethylene carbonate (EC): ethyl methyl carbonate (EMC) (3:7 w/w) electrolyte, improves cell capacity retention with higher retention seen at higher additive contents. We show that reducing the lower cutoff voltage (LCV) of full cells to 2.5 V increases the Si-Gr electrode potential to 1.12 V vs. Li/Li + ; this relatively-high delithiation potential correlates with the lower capacity retention displayed by the cell. Furthermore, we show that raising the upper cutoff voltage (UCV) can increase cell energy density without significantly altering capacity retention over 100 charge-discharge cycles.